Immunotherapies for Anti-N-M-methyl-D-aspartate Receptor Encephalitis: Multicenter Retrospective Pediatric Cohort Study in China - Guang, Shiqi; Ma, Jiannan; Ren, Xiaotun; Zhou, Shuizhen; Yang, Jian; Zhang, Jianzhao; Cao, Xiaoshuang; Zhong, Linxiu; Ding, Xiao; Wang, Xiaosu; Ren, Changhong; Zhang, Weihua; et al. (Frontiers in Pediatrics, 2021)
Background: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis has been discovered for more than a decade, but the establishment of standardized immunotherapy protocol for pediatric patients still needs more clinical evidence. Methods: A multicenter, retrospective study was conducted on pediatric patients diagnosed with anti-NMDAR encephalitis between November 2011 and December 2018. The clinical records including clinical manifestations, immunotherapy strategies, and outcomes were collected and analyzed. Results: A total of 386 patients were included in our study and the median onset age was 8.00 (IQR 4.83–10.90) years. All patients received first-line immunotherapy and the majority (341, 88.3%) used the standard combination of methylprednisolone pulses (MEP) and intravenous immunoglobulins (IVIG), but 211 patients did not show satisfactory improvement (mRS ≥ 3). Mainly three treatment strategies were applied after first-line immunotherapy: second-line immunotherapy, repetitive first-line immunotherapy, and maintaining oral prednisolone. For patients with mRS ≥ 4 after first-line immunotherapy, the incidence of poor outcome (mRS ≥ 3) in oral prednisolone group was higher than that in other treatment groups (p = 0.039). No difference in complete recovery rate (mRS = 0) was found between patients receiving second-line and repetitive first-line immunotherapy, or patients using long-term and short-term prednisolone. Out of 149 patients who received anti-myelin oligodendrocyte glycoprotein antibody (MOG-Ab) test, 27 (18.12%) were positive. Patients with concomitantly positive MOG-Ab showed milder conditions compared to patients with typical anti-NMDAR encephalitis and were more inclined to relapses. We also identified female, MOG-Ab positive, and not receiving second-line and/or repetitive first-line immunotherapy were risk factors for relapses. Conclusions: For patients with mRS ≥ 4 after first-line immunotherapy and patients with concomitantly positive MOG-Ab, second-line immunotherapy is recommended. When second-line immunotherapy is not applicable, repetitive first-line immunotherapy can be considered as an option. Both second-line and repetitive first-line immunotherapy are beneficial to reduce relapse rate. The duration of sequential oral prednisolone can be shortened after fully evaluating patients' conditions.